ANALISIS MINAT SISWA DALAM MENGIKUTI EKSTRAKURIKULER BOLA BASKET DI SMP NEGERI 1 SUKATANI - Faiq Fauzan Ruspendi; Dhika Bayu Mahardhika; Rahmat Iqbal (Jurnal Porkes, 2026)
This study was motivated by the disparity in student interest in participating in the basketball extracurricular program at SMP Negeri 1 Sukatani, where, out of 30 students, only 40% actively participated in practice, while the remaining 60% were less active. This study aims to describe students’ interest, identify the factors influencing it, and analyze the impact of interest on students’ performance. The study employed a qualitative approach using descriptive methods. The research subjects were 30 students participating in the extracurricular program, with 6 students and 1 coach selected through purposive sampling to serve as informants. Data collection techniques included observation, semi-structured interviews, and documentation. Data analysis utilized the Miles and Huberman model. The results indicate that students’ interest is relatively high, shaped by a combination of internal and external factors. External factors are more dominant in the initial stages of interest, while internal factors play a role in maintaining consistent participation. High interest has a positive impact on discipline, physical fitness, focus on learning, and improved basketball skills. However, there are still 10 students (33%) who are less active due to barriers such as distance from home, lack of self-confidence, and limited facilities. In conclusion, student interest plays a crucial role in the success of the basketball extracurricular program at SMP Negeri 1 Sukatani.